The human intellect, divine revelation and knowledge based on Al-Qaradowi's work: al-'Aql wa al-'Ilm fi al-Qur'an al-Karim - Hassan, Mohd. Kamal (Kulliyyah of Science, IIUM, 2011)
While reaffirming the supremacy of Divine revelation, al-QaraÌÉwÊ explains that the sound human intellect has been entrusted by Divine revelation to play crucial roles in the confirmation of revealed truths and the development of all fields of human knowledge necessary for effective and wholesome human vicegerency on earth. There should not be, however, any conflict between revelation and reason. A fuller exposition of this epistemological dimension of the Islamic worldview is given in his book al-ÑAql wa al-ÑIlm fi al-Qur’Én al-KarÊm which was published in 1996. The importance of the use of the human intellect for thinking, reflection, understanding, knowing, pondering and contemplation is reflected by the Qur’Énic use of several verbs which convey the aforementioned functions. The verb Ñaqala (to use one’s intelligence, to comprehend, to understand, to think) is used in its present tense (second person plural, masculine and third person plural masculine) – taÑqilËn and yaÑqilËn – 46 times in the Qur’Én while the verbs Ñaqala, naÑqilu and yaÑqilu occur once each. The expression “afalÉ taÑqilËn” (Will you not understand? Or Have you then no sense?) occurs 13 times. The expression is used to convey AllÉh’s exhortation or admonishment to human beings for having double standards (Q. Al-Baqarah 2: 44); for neglecting the Hereafter and being deceived by worldly pleasures despite knowing God’s Scripture (Q. Al-AnÑÉm 6: 32, Q. Al-‘A’rÉf 7: 169, Q. YËsuf 12: 109); for ignoring the message of the Qur’Én (Q. Al-anbiyÉ’ 21: 10); for not understanding the powers of AllÉh (S.W.T) in giving life and causing death (Q. Al-Mu’minËn 23: 80); for not realizing that the false gods worshipped by human beings could not bring benefit nor harm them (Q. Al-AnbiyÉ 21: 63-67). In these verses the Qur’Én reprimands human failure to use the God-given intellect to strengthen true religious faith.